2012
DOI: 10.5539/elt.v5n7p42
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Writing Apprehension Level and Self-efficacy Beliefs on Writing Proficiency Level among Pre-university Students

Abstract: The purpose of this study was to determine the level of writing apprehension and how writing apprehension level and writing self-efficacy beliefs influences writing proficiency level among pre-university students. Participants were 320 pre-university students from a northern region college offering this programme. All the respondents were administered with three instruments measuring their writing apprehension levels and writing self-efficacy beliefs and their writing proficiency. The writing apprehension leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
10
1
Order By: Relevance
“…Furthermore, Zhang (2011) Cheng (2004a) found a significant negative relationship between writing anxiety and writing performance of the participants. Finally, Singh and Rajalingam (2012) reported that there was a positive relationship between L2 writing anxiety and writing performance. In the current study, however, 91 out of 117 participants had high grades and 38 of them had a high level of anxiety.…”
Section: Discussion Conclusion and Pedagogical Implicationsmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, Zhang (2011) Cheng (2004a) found a significant negative relationship between writing anxiety and writing performance of the participants. Finally, Singh and Rajalingam (2012) reported that there was a positive relationship between L2 writing anxiety and writing performance. In the current study, however, 91 out of 117 participants had high grades and 38 of them had a high level of anxiety.…”
Section: Discussion Conclusion and Pedagogical Implicationsmentioning
confidence: 98%
“…To illustrate, DeDeyn (2011) indicated that there was no significant correlation between students' writing performance and writing anxiety levels. On the other hand, Singh and Rajalingam (2012) examined how writing anxiety level and writing self-efficacy beliefs influenced writing proficiency level. The participants were 320 Malaysian pre-university students.…”
Section: L2 Writing Anxiety and Writing Performancementioning
confidence: 99%
See 2 more Smart Citations
“…This community is based on common histories, goals, and routines (Graham, 2018); positions writers to discuss ideas with one another before writing on their own (Vygotsky, 1978); and helps to build self‐efficacy in writers through positive writing experiences (Bandura, 1986; Dunlap, 2006; Fritson, 2008). Singh and Rajalingam (2012) found that these types of experiences can inspire future success, and several researchers (Bromley & Powell, 1999; Cisero, 2006; Fritson, 2008; Julien, 2017; Linares, 2020; Portman, 2020) asserted that writing as a social activity can motivate writers and lessen their aversions toward writing.…”
Section: Figurementioning
confidence: 99%